Metabolic Pancreatitis: Pancreatic Steatosis, Hypertriglyceridemia, and Associated Chronic Pancreatitis in 3 Patients with Metabolic Syndrome - Melitas, Constantine (Case Rep Gastroenterol, 2018)
Obesity, insulin resistance, and metabolic syndrome continue to increase in prevalence. Hypertriglyceridemia is commonly associated and represents a valuable marker of metabolic syndrome. An increase in subcutaneous fat deposition places patients at risk for visceral adipose deposition in sites such as the liver, heart, and pancreas. Pancreatic steatosis in the setting of metabolic syndrome is a rapidly emerging entity whose clinical spectrum remains to be defined. Hypertriglyceridemia is an accepted cause of acute pancreatitis but its role in chronic pancreatic injury remains to be explored. We present 3 patients with chronic abdominal pain and pancreatic steatosis in the setting of underlying metabolic syndrome with hypertriglyceridemia. These cases were identified in one endoscopic ultrasonographer's practice over a 12-month period. Each patient had documented hypertriglyceridemia but no history of acute hypertriglyceride-induced pancreatitis. A history of significant alcohol exposure was carefully excluded. Each patient underwent endoscopic ultrasonography (EUS) which proved critical in delineating the spectrum of chronic pancreatic injury. Each of our patients had EUS documentation of pancreatic steatosis and sufficient criteria to establish a diagnosis of chronic pancreatitis. Intraductal pancreatic calculi were identified in all 3 patients. Our series suggests that in the setting of metabolic syndrome, chronic hypertriglyceridemia and pancreatic steatosis may be associated with chronic pancreatitis. We hypothesize that hypertriglyceridemia may provide a pathogenic role in the development of chronic pancreatic microinjury. In addition, each of our patients had EUS-documented pancreatic ductal lithiasis. To our review, these are novel findings which have yet to be reported. We believe that with an enhanced awareness, it is likely that the entity of metabolic syndrome with features of pancreatic steatosis and hypertriglyceridemia with their associated manifestations of chronic pancreatitis, including ductal lithiasis, will be widely appreciated.